Surface plasmon-assisted optical bistability in the quantum dot-metal nanoparticle hybrid system. Issue 13 (19th July 2016) - Bao, Chengjun; Qi, Yihong; Niu, Yueping; Gong, Shangqing
Abstract : We theoretically investigated optical bistability (OB) of a coupled excition–plasmon hybrid system in a unidirectional ring cavity. It is found that the threshold and the region of OB can be tuned by adjusting the center–center distance between the quantum dot and metal nanoparticle (MNP), the Rabi frequency of the control field and the radius of the MNP. Due to the significantly enhanced optical nonlinearity by the surface plasmon effect, the threshold of OB can be decreased greatly when the probe field is parallel to the major axis of the hybrid system. The enhanced OB may have promising applications in optical switching and optical storage.